2018
DOI: 10.21451/1984-3143-ar2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technologies (ART) in water buffaloes

Abstract: Our expanding knowledge of ovarian function during the buffalo estrous cycle has given new approaches for the precise synchronization of follicular development and ovulation to apply consistently assisted reproductive technologies (ART). Recent synchronization protocols are designed to control both luteal and follicular function and permit fixed-time AI with high pregnancy rates during the breeding (autumn-winter) and nonbreeding (springsummer) seasons. Additionally, allow the initiation of superstimulatory tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 78 publications
2
33
0
1
Order By: Relevance
“…Derived from the problems in grading more buffalo oocytes were classified viable compared with cattle 94.7% vs. 83.3% (p=0.356), almost all oocytes were cultured, the results obtained in cattle are not different than others [26]. Baruselli et al, inform in buffalo oocytes lower viability rate of 50% [32]. Despite that viability could be a subjective parameter, the effect of over cleavage rate and blastocyst rate is important, especially in this paper that it contributes to the lower parameters obtained here.…”
Section: Embryo Productionmentioning
confidence: 99%
“…Derived from the problems in grading more buffalo oocytes were classified viable compared with cattle 94.7% vs. 83.3% (p=0.356), almost all oocytes were cultured, the results obtained in cattle are not different than others [26]. Baruselli et al, inform in buffalo oocytes lower viability rate of 50% [32]. Despite that viability could be a subjective parameter, the effect of over cleavage rate and blastocyst rate is important, especially in this paper that it contributes to the lower parameters obtained here.…”
Section: Embryo Productionmentioning
confidence: 99%
“…Para lograr el máximo rendimiento, el conocimiento de la fisiología reproductiva es de gran importancia, si bien algunos aspectos coinciden con las vacas, existen particularidades que hacen a los búfalos una especie única, y por tanto es necesario conocerlas, no solo para identificar y controlar factores que pudiesen afectar el desempeño reproductivo sino también para la adecuada aplicación de diferentes biotecnologías reproductivas, cuyo uso se ha incrementado en los últimos años (Berdugo Gutiérrez, 2012;Baruselli et al, 2018). Además el estudio de la fisiología reproductiva de la especie bufalina se hace cada vez más necesario dado que la especie ha sido sometida a programas de mejora genética observándose un incremento en la producción de leche (Ahmad et al, 2009;Fooda et al, 2010;Menéndez-Buxadera y Verde, 2014), y algunas investigaciones han reportado una relación negativa entre la producción de leche y la eficiencia reproductiva (Abayawansa et al, 2011;Jamuna y Chakravarty, 2016;Nava-Trujillo et al, 2018;Nava-Trujillo et al, 2019c).…”
Section: Introduccionunclassified
“…There was showed that farm affected the OPU/IVEP efficiency, showing that animal management has an important influence on the application of reproductive technologies (BARUSELLI et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…OPU is a very versatile technique that allows a repeated production of embryos from donors of genetic value and it is a serious alternative to in vivo superovulation. It represents a valid system to recover oocytes from living donors, in almost any physiological status (prepubertal, pubertal, non-pregnant cow or pregnant up to the third or fourth month) (GALLI et al, 2001;BAYEUX et al, 2017;BARUSELLI et al, 2018). In buffalo it is reported a high individual variability in the number of oocytes retrieved per OPU (from 0 to 30), with a mean of 8.9 ± 5.0 per donor, and hence in the number of embryos produced, making it necessary to distinguish between desirable and undesirable donors (BARUSELLI et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation